Service productivity management : improving service performance using data envelopment analysis (DEA) - Sherman, H. David (Springer, 2006)
"Service Productivity Management systematically explores complex service issues and suggests the most appropriate methods to improve service productivity, quality, and profitability. The book provides insights and methods to answer questions on a range of productivity issues: How do you manage profitability of a network of hundreds or thousands of branch offices disbursed over several states and countries? How can managed-care organizations manage the quality and cost of hundreds of physicians providing health services to millions of plan members? What methods would enable a government to ensure that the multiple offices serving citizens across a country are operating at low cost while meeting the required service quality?